MELAWAN PARTAI POLITIK: STRATEGI CALON PERSEORANGAN DALAM MEREBUT SUARA DI PEMILUKADA SLEMAN TAHUN 2010 - KURNIAWAN, HAMDAN; Dwipayana, AAGN Ari ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This paper examines the strategies candidates win votes in the General Election. Strategies used include mobilizing support for the nomination, the mobilization of funds, organizing the campaign team and manage the campaign. Practice using the four strategies are used as a foundation to see similarities in reasoning strategy by candidates promoted by political parties. The research was conducted in Sleman, which organized the election of regional heads directly for the second time, but the first time and became the only district in the Province of DIY that accommodate individual candidate. The presence of candidates initially welcomed joy because they offer a change. He is an enriching alternative options, in the middle of the saturation of the political parties are increasingly oligarkhis, closed, pragmatic and suffered a number of other diseases. However, political reality speaks otherwise. Candidates actually showed character, the character and nature are almost identical to the candidates of political parties. The way they build support in the process kandidasi alike follow the logic of transactional, who bartered support with some money. Similarly, the mobilization of funds that have a tendency to rely entirely on the shoulders of the candidate's campaign expenses. We also encountered the same symptoms in a strategy of organizing the team that laid the activist and former political parties into the circle of the campaign team of candidates. Further consequence that we encounter is that the planning and campaign management can not be separated from the mindset of those involved in it. The approach is still based political parties even though they declare as candidates and political parties standing opposite. The depth of interaction with political parties and independent candidates desire to embrace all the elements have been dragging them into the dark hole of identity. Candidates can not be called independent, nor as a representation of political parties..Thickness and clarity difficult to measure with certainty. In these cases, candidates failed to show that he was different from political parties. He is such not within the political parties. Little wonder then that arises is the individual candidate with a taste of political parties. This study clarifies the position of independent candidates in local political arena. Individual paths is the way out for anyone who want to taste the contestation of election but difficult to penetrate the space provided kandidasi political party. He is just an alternative door and can not be automatically called and sterile altogether different from the political parties. The difference or similarity is determined more by factors of background candidates. The more viscous blood ties with political parties, the greater the tendency of the similarity method and reasoning strategy by political parties.